Pathways to post-capitalist tourism. Issue 2 (3rd April 2023) - Fletcher, Robert; Blanco-Romero, Asunción; Blázquez-Salom, Macià; Cañada, Ernest; Murray Mas, Ivan; Sekulova, Filka
Abstract: Potential to identify and cultivate forms of post-capitalism in tourism development has yet to be explored in depth in current research. Tourism is one of the world's largest industries, and hence a powerful global political and socio-economic force. Yet numerous problems associated with conventional tourism development have been documented over the years, problems now greatly exacerbated by impacts of the ongoing COVID-19 pandemic. Calls for sustainable tourism development have long sought to address such issues and set the industry on a better course. Yet such calls tend to still promote continued growth as the basis of the tourism industry's development, while mounting demands for "degrowth" suggest that growth is itself the fundamental problem that needs to be addressed in discussion of sustainability in tourism and elsewhere. This critique asserts that incessant growth is intrinsic to capitalist development, and hence to tourism's role as one of the main forms of global capitalist expansion. Touristic degrowth would therefore necessitate postcapitalist practices aiming to socialise the tourism industry. While a substantial body of research has explored how tourism functions as an expression of a capitalist political economy, thus far no research has systematically explored what post-capitalist tourism might look like or how to achieve it. Applying Erik Olin Wright's 2019 innovative typology for conceptualizing different forms of post-capitalism as components of an overarching strategy for "eroding capitalism" to a series of illustrative allows for exploration of their potential to contribute to an analogous strategy to similarly "erode tourism" as a quintessential capitalist industry.